2017
DOI: 10.1016/j.psychres.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

The impact of stigma on emotional distress and recovery from psychosis: The mediatory role of internalised shame and self-esteem

Abstract: Internalised shame and self-esteem have both been proposed to play an integral role in the relationship between stigma and its negative psychological sequelae in people who experience psychosis, but there has been little quantitative exploration to examine their roles further. The aim of this study was to examine the relationship of stigma (experienced and perceived) with emotional distress and recovery in psychosis, and to examine internalised shame and self-esteem as potential mediators. A total of 79 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 39 publications
4
32
1
4
Order By: Relevance
“…The link between the appraisal of stigma as harmful (perceived harm subscale of the SSS) and social rejection and isolation was supported in the current study. However, the absence of a correlation between perceived harm and internalised shame was not predicted as previous mental health literature has found that internalised shame plays an integral role in shaping stigma experiences (40,48). In addition, the SSS total and the ability to cope subscales did not show correlations with internalised shame.…”
Section: Findings In the Context Of Existing Researchcontrasting
confidence: 60%
“…The link between the appraisal of stigma as harmful (perceived harm subscale of the SSS) and social rejection and isolation was supported in the current study. However, the absence of a correlation between perceived harm and internalised shame was not predicted as previous mental health literature has found that internalised shame plays an integral role in shaping stigma experiences (40,48). In addition, the SSS total and the ability to cope subscales did not show correlations with internalised shame.…”
Section: Findings In the Context Of Existing Researchcontrasting
confidence: 60%
“…The link between the appraisal of stigma as harmful (perceived harm subscale of the SSS) and social rejection and isolation was supported in the current study. However, the absence of a correlation between perceived harm and internalized shame was not predicted as previous mental health literature has found that internalized shame plays an integral role in shaping stigma experiences (42,50). The SSS may not adequately measure the stigma stress appraisal process for people living with dementia.…”
Section: Findings In the Context Of Existing Researchmentioning
confidence: 70%
“…Although it is important to cater to the individual, adherence can be maximized through a combination of group and individual work (Ward, White, & Druss, 2015). In a recent qualitative exploration of the effects and determinants of exercise participation in people with FEP, Firth, Carney, Jerome, et al (2016) found both autonomy (eg, choosing the activity) and social support (eg, having an exercise buddy) to be critical factors in engaging participants; in contrast, anxiety and lack of motivation were key barriers.…”
Section: Early Intervention Greatly Reduces Chance Of Chronic Illnessmentioning
confidence: 99%
“…In that way, sport is more powerful than politics” (Bailey, , p. 85). The reach of sport is especially important in regards to FEP recovery when the previously discussed stigmatising properties of psychotic illness are considered (eg, Wood, Byrne, Burke, Enache, & Morrison, ). Beyond its potential to be a uniting force, sport also offers many health benefits.…”
Section: Physical Activity Is Important For Psychosis Recovery and Prmentioning
confidence: 99%